2006
DOI: 10.1001/archpedi.160.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Abstinence Syndrome After In Utero Exposure to Selective Serotonin Reuptake Inhibitors in Term Infants

Abstract: Neonatal abstinence syndrome occurs in 30% of neonates exposed to SSRIs in utero. These neonates should be monitored for at least 48 hours after birth. The long-term effects of prolonged exposure to SSRIs, particularly in neonates who develop severe symptoms, have yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
234
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(242 citation statements)
references
References 27 publications
6
234
1
1
Order By: Relevance
“…In the context of prenatal SSRI exposure, the study by Berard et al 74 highlights the critical importance of accounting for dose effects; the association between paroxetine and cardiac defects was not significant until outcomes were stratified by daily dose of paroxetine. A dose effect has also been demonstrated for birth outcomes 24,47 although not all studies have replicated such an effect 20,29,64 . However, investigations of a dose effect have often been conducted utilising groups of infants with different SSRI exposure types.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the context of prenatal SSRI exposure, the study by Berard et al 74 highlights the critical importance of accounting for dose effects; the association between paroxetine and cardiac defects was not significant until outcomes were stratified by daily dose of paroxetine. A dose effect has also been demonstrated for birth outcomes 24,47 although not all studies have replicated such an effect 20,29,64 . However, investigations of a dose effect have often been conducted utilising groups of infants with different SSRI exposure types.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Fluoxetine exposure in the second and third trimester was reportedly associated with increased neonatal adaptation problems 36 , with a similar pattern reported for paroxetine and respiratory distress 35 . The study by Levinson-Castiel et al 47 reported a significant correlation between dose of paroxetine and severity of neonatal symptoms.…”
Section: Neonatal Adaptationmentioning
confidence: 97%
See 2 more Smart Citations
“…In most cases, the symptoms appear within the first 8 hours of delivery and persist for the first 2-6 days of life. It is believed that the syndrome will not develop if there are no symptoms within the first two days of life [34]. Withdrawal symptoms and toxicity symptoms are largely overlapping, which is why differentiation based on the clinical picture is extremely difficult.…”
Section: Poor Neonatal Adaptation Syndrome (Pnas)mentioning
confidence: 99%